A Troubled Past: Fieldworking in a Contested Place (Journal of Comparative Social Work, 2011)
The aim of this study is to demonstrate how political meaning is manifested with the aid of monuments, and to look at how other material objects also become invested with political ideology and are eventually incorporated by citizens and filled with meaning and affective power. For this project, a phenomenological approach was deemed to be the most suitable. The classical hierarchy between visiting researchers and native informants was overcome by the active and equitable participation of local scholars.